The devil's tomb - Gooding, Cuba, 1968-; Manning, Taryn; Rollins, Henry, 1961-; Ward, Zack, 1970-; Cruz, Valerie; London, Jason; G., Franky, 1965-; Jacobsen, Stephanie, 1980-; Fobbs, Brandon; Moseley, Bill, 1951-; Winstone, Ray, 1957-; Perlman, Ron, 1950-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
"When the scientist leading a top-secret Middle Eastern archeological site goes missing, an elite military unit is sent on a search and rescue mission. Descending deep below civilization, Captain Mack and his team soon find themselves face to face with an ancient evil. An evil that may not be of this world."--Container.
DVD; Dolby digital 5.1; region 1.
Soundtrack and subtitles in English or French.
Closed-captioned.
Title and credits from container.
Cuba Gooding, Jr., Taryn Manning, Henry Rollins, Zack Ward, Valerie Cruz, Jason London, Franky G, Stephanie Jacobsen, Brandon Fobbs, Bill Moseley, Ray Winstone, Ron Perlman.
Director of photography, Thomas Callaway ; editor, Chris Conlee ; music by Bill Brown.
Keywords: Scientists -- Middle East -- Drama; Archaeology -- Middle East -- Drama; Search and rescue operations -- Middle East -- Drama; Good and evil -- Drama; Scientists -- Middle East -- Fiction; Archeology -- Middle East -- Fiction; Rescue work -- Middle East -- Fiction; Good and evil -- Fiction; Closed caption video recordings; Videodiscs; Feature films; Fiction films; Video recordings for the hearing impaired; Thrillers (Motion pictures); Feature films; Thrillers (Motion pictures); Action and adventure films; Horror films; Science fiction films; DVD-Video discs